2021
DOI: 10.1002/macp.202100221
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical/Photochemical, Kinetic, and Migration Stability Studies of One‐Component Polymerizable Thioxanthone‐Based Photoinitiators

Abstract: Herein, N‐benzyl‐N‐(9‐oxo‐9H‐thioxanthen‐2‐yl)acrylamide (TXNBA) is designed and synthesized as one‐component polymerizable photoinitiator (PI). It is investigated in terms of its photophysical/photochemical, kinetic, and migration stability properties by ultraviolet‐visible spectrophotometer, Fourier transform infrared spectrometer, and EPR spin trapping experiments. In conjunction with the experimental studies, series of density functional theory calculations are performed and various photophysical and photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Kreutzer et al [16] reported two Schiff base PIs (TX-EDA and TX-DETA) could initiate FRP. In our previous work, the polymerizable PIs, such as 4-((methyl(9-oxo-9H-thioxanthen-2yl)amino)methyl)phenyl acrylate (TX-PA), [17] ((4-((methyl(9-oxo-9H-thioxanthen-2-yl)amino)methyl)benzyl)-azanediyl) bis(ethane-2,1-diyl) diacrylate (TX-BDA), [18] and N-benzyl-N-(9oxo-9H-thioxanthen-2-yl)acrylamide (TXNBA) [19] were studied with efficient photoinitiated properties and high migration stability. We are dedicated to looking for efficient PIs that are simpler to synthesize and have better storage stability.…”
Section: Introductionmentioning
confidence: 99%
“…Kreutzer et al [16] reported two Schiff base PIs (TX-EDA and TX-DETA) could initiate FRP. In our previous work, the polymerizable PIs, such as 4-((methyl(9-oxo-9H-thioxanthen-2yl)amino)methyl)phenyl acrylate (TX-PA), [17] ((4-((methyl(9-oxo-9H-thioxanthen-2-yl)amino)methyl)benzyl)-azanediyl) bis(ethane-2,1-diyl) diacrylate (TX-BDA), [18] and N-benzyl-N-(9oxo-9H-thioxanthen-2-yl)acrylamide (TXNBA) [19] were studied with efficient photoinitiated properties and high migration stability. We are dedicated to looking for efficient PIs that are simpler to synthesize and have better storage stability.…”
Section: Introductionmentioning
confidence: 99%